2018
DOI: 10.1080/15592294.2018.1507199
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant imprinting in mouse trophoblast stem cells established from somatic cell nuclear transfer-derived embryos

Abstract: Although phenotypic abnormalities frequently appear in the placenta following somatic cell nuclear transfer (SCNT), mouse trophoblast stem cells (TSCs) established from SCNT embryos reportedly show no distinct abnormalities compared with those derived from normal fertilization. In this study, we reexamined SCNT-TSCs to identify their imprinting statuses. Placenta-specific maternally imprinted genes (Gab1, Slc38a4, and Sfmbt2) consistently showed biallelic expression in SCNT-TSCs, suggesting their loss of impri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…In the following, these clusters are referred to as the Sfmbt2 and Mirg miRNAs, respectively. The altered expression levels of these miRNAs might reflect the status of their host gene (Sfmbt2) and the imprinting center (intergenic differentially methylated region), respectively, because both are known to exhibit LOI in SCNT placentas 14 and SCNT-derived trophoblast stem cells (TSCs) 31 . Scatterplots showing the variations in the expression of all the miRNA genes between IVF and wild type SCNT placentas clearly distinguished the Sfmbt2 miRNAs and Mirg miRNAs from other genes based on their upregulation and downregulation, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the following, these clusters are referred to as the Sfmbt2 and Mirg miRNAs, respectively. The altered expression levels of these miRNAs might reflect the status of their host gene (Sfmbt2) and the imprinting center (intergenic differentially methylated region), respectively, because both are known to exhibit LOI in SCNT placentas 14 and SCNT-derived trophoblast stem cells (TSCs) 31 . Scatterplots showing the variations in the expression of all the miRNA genes between IVF and wild type SCNT placentas clearly distinguished the Sfmbt2 miRNAs and Mirg miRNAs from other genes based on their upregulation and downregulation, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicated that epigenetic modifications were altered in cloned abnormal animals compared to naturally bred ones. Global hypo-acetylation, reduced DNA methylation in satellite I region, loss of imprinting (LOS), reduced histone methylation were reported in the somatic cell nuclear transfer derived animals [29,30,31]. Piglets derived by SCNT also showed a higher incidence of malformations and a higher death rate during the perinatal period [32].…”
Section: Discussionmentioning
confidence: 99%
“…The unusual DNA methylation pattern mostly exists on the satellite sequence, long terminal repeat sequence, long dispersed elements (LINEs), and imprinted control region (ICR). Trophoblast cells in SCNT blastocysts are hypermethylated in intergenic differentially methylated regions, which are associated with subsequent abnormal placental development [30]. Treatment with a methyltransferase inhibitor and interference of Dnmts have been used to reduce the higher DNA methylation level, and this strategy effectively improves the SCNT efficiency [28].…”
Section: Dna Methylationmentioning
confidence: 99%